Imalawan - Trampe, Fe Esperanza (Likhaan: The Journal of Contemporary Philippine Literature; Vol 18 No 1 (2024): LIKHAAN 18 The Journal of Contemporary Philippine Literature, 2024)
“Imalawan” is a short story based on the real Islet of Imalawan in Palawan’s Cuyo Archipelago. It seeks to tackle, through a magic realist lens, the pressing concerns of those who live in the remote island municipalities of Cuyo and Magsaysay. Prior to the advent of technology, myths and legends were passed around to explain certain phenomena. While these stories are often fantastic in nature, they remain rooted in truths about the communities they come from. “Imalawan” is a contemporary Filipino story that aims to reveal some of these truths.